Systematic review of fit note use for workers in the UK. Issue 7 (7th May 2018) - Dorrington, Sarah; Roberts, Emmert; Mykletun, Arnstein; Hatch, Stephani; Madan, Ira; Hotopf, Matthew
Abstract : Objectives: The fit note, introduced in England, Wales and Scotland in 2010, was designed to change radically the sickness certification process from advising individuals on their inability to work to advising them on what they could do if work could be adapted. Our review aimed to evaluate the following: (1) Is the 'maybe fit' for work option being selected for patients? (2) Are work solutions being recommended? (3) Has the fit note increased return to work? (4) Has the fit note reduced the length of sickness absence? We considered the way in which outcomes vary according to patient demographics including type of health problem. Methods: Studies were identified by a systematic search. We included all studies of any design conducted in the UK with working age adults, aged 16 or over, from 1 April 2010 to 1 Nov 2017. Risk of bias was assessed using a modified Newcastle-Ottawa Scale. Results: Thirteen papers representing seven studies met inclusion criteria. In the largest study, 'maybe fit' for work was recommended in 6.5% of fit notes delivered by general practitioners (GP; n=361 801) between April 2016 and March 2017. 'Maybe fit' recommendations were made in 8.5%–10% of fit notes received by primary care patients in employment, and in 10%–32% of patients seen by GPs trained in the Diploma in Occupational Medicine. 'Maybe fit' was recommended more for women, those with higher socioeconomic status, and for physical, as opposed to psychiatric disorders. The majority of fit notes with the 'maybe fit' option selected included work solutions. There was inconclusive evidence to suggest that the introduction of the fit note has reduced sickness absence among patients in employment. Conclusions: Fit notes represent a major shift in public policy. Our review suggests that they have been incompletely researched and not implemented as intended.